(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article analyzes the effectiveness of using the Internet service «Baamboozle» as a means of activating motivation and involvement of students of the Fiscal Institute under the Tax Committee of the Republic of Uzbekistan in the process of learning English. It is assumed that learning English will become more effective when creating a gamified environment in the classroom using the Internet service «Baamboozle». The article describes trial training using the Internet service «Baamboozle», analyzes its results, which showed that the use of the Internet service «Baamboozle» when creating a gamified environment in English classes significantly increases students’ motivation and involvement in the learning process.